Late diagnosis of mucopolysaccharidosis type IVB and successful aortic valve replacement in a 60-year-old female patient - Dostalova, Gabriela; Hlubocka, Zuzana; Lindner, Jaroslav; Hulkova, Helena; Poupetova, Helena; Vlaskova, Hana; Sikora, Jakub; Linhart, Ales; Zeman, Jiri; Magner, Martin (Cardiovascular pathology, 2018)
Mucopolysaccharidosis type IVB (MPS IVB) is a very rare lysosomal storage disorder characterized by skeletal dysplasia, hearing disorder, and cardiac valvular disease. Herein, we report an extremely rare manifestation of MPS IVB in a 60-year-old female patient who underwent a successful aortic valve replacement. The patient presented with mild coarse facial features, short stature, mild dyspnea, sternal protrusion, mild lumbar hyperlordosis, and waddling gait owing to bilateral femoral head necroses and bilateral arthrosis of the knees. The patient also suffered from dyspnea, NYHA II-III. Echocardiography revealed severe stenosis of a calcified aortic valve (AVA 0.67 cm2, AVAi 0.45 cm2/m2, PG max/mean 130/80 mmHg), left ventricular hypertrophy with predominant septal thickening (18 mm) and mild left ventricle outflow tract obstruction at rest, mild mitral valve regurgitation, and dilated ascending aorta (36 mm, 26.5 mm/m2). Dyspnea resolved after septal myectomy and replacement of the aortic valve with bioprosthesis. Excretion levels and spectrum of glycosaminoglycans (GAGs) in urine were normal in the patient. We confirmed the diagnosis of MPS IVB by identifying decreased beta-galactosidase activity in isolated leukocytes (6 nmol/h/mg; controls 95-272) and by molecular genetic analyses (c.438_440delTCT and c.817_818TG>CT mutations in the GLB1 gene). Primary lysosomal storage of glycosaminoglycans was detected in fibroblasts of the aortic valve. Additional pathologies included valvular fibrosis, calcification, neovascularization, and mild chronic inflammation. In conclusion, the diagnosis of MPS IVB should be considered in older patients with cardiac valvular disease and progressive skeletal abnormality even if urinary excretion levels of GAGs are normal.
Keywords: Delayed Diagnosis; beta-galaktosidasa; Aortic Valve; echokardiografie; opožděná diagnóza; Time Factors; Mucopolysaccharidosis IV; beta-Galactosidase; výsledek terapie; DNA Mutational Analysis; Echocardiography; Middle Aged; Biopsy; mutace; Calcinosis; Aortic valve replacement; Heart Valve Prosthesis; mutační analýza DNA; aortální chlopeň; Mucopolysaccharidosis type IVB; chirurgická náhrada chlopně; Aortic Valve Stenosis; bioprotézy; Progressive skeletal disease; magnetická rezonanční tomografie; mukopolysacharidóza IV; Heart Valve Prosthesis Implantation; Magnetic Resonance Imaging; kalcinóza; ženské pohlaví; Mutation; Bioprosthesis; Humans; srdeční chlopně umělé; časové faktory; lidé středního věku; biopsie; aortální stenóza; Female; Treatment Outcome; lidé